(untitled) (Communication & Society, 2022)
This article analyzes the news coverage of the COVID-19 health crisis by Televisión Española (TVE1), to determine if this media reported the news with rigor and in accordance with journalism professional codes and best practice guidelines. For this purpose, content analysis was conducted on the universe of news stories (n=1,449) in the TVE1 daily newscast, starting with the first outbreak of the pandemic on the Iberian Peninsula on February 26, 2020, until the end of the first state of emergency on June 21, 2020. Our categories of analysis were: information sources, news frames, predominant topics, resources used for dramatic effects, and breaches of journalism ethics in reporting news. In general, TVE1 did not engage in sensationalized or dramatized news coverage, but instead attempted to transmit a message that was educational and instructional. Its policy was to provide information on measures adopted by authorities to help prevent the spread of the pandemic. Nevertheless, TVE’s benevolent attitude towards the government and its policies can be observed in its news reporting, revealing a lack of impartiality and editorial independence by this media. Despite the importance of specialized and expert information in times of a pandemic, eyewitness sources were those most used in reporting news, even in economic news framing. Furthermore, these latter sources were employed instead of expert ones, which were in fact the least used, and whose presence progressively declined during the analyzed period.